2008
DOI: 10.1051/0004-6361:200810907
|View full text |Cite
|
Sign up to set email alerts
|

SiO outflow signatures toward massive young stellar objects with linearly distributed methanol masers

Abstract: Context. Methanol masers are often found in linear distributions, and it has been hypothesized that these masers trace circumstellar accretion disks around young massive stars. However, recent observations in H 2 emission have shown what appear to be outflows at similar angles to the maser distribution angles, not perpendicular as expected in the maser-disk scenario. Aims. The main motivation behind the observations presented here is to use presence and morphology of an independent outflow tracer, namely SiO, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 44 publications
5
37
1
Order By: Relevance
“…One can speculate that the mid-infrared photons, required for pumping the 6.7 GHz masers (Cragg et al 2002), could more easily penetrate into the dense HMC gas in proximity of the outflows, taking advantage of the cavities induced by the outflowing gas. The proposed association of the 6.7 GHz masers with outflows, based on the similarity of the 3D velocities of the methanol and water masers, agrees with the results by De Buizer (2003) and De Buizer et al (2009), which find that in most cases the methanol masers are elongated parallel to jets traced by the H 2 and SiO emissions, suggesting a physical association of the 6.7 GHz masers with the corresponding outflows.…”
Section: Methanol and Oh Maser Dynamics: Jet-driven Expansion Of The Hmcsupporting
confidence: 89%
“…One can speculate that the mid-infrared photons, required for pumping the 6.7 GHz masers (Cragg et al 2002), could more easily penetrate into the dense HMC gas in proximity of the outflows, taking advantage of the cavities induced by the outflowing gas. The proposed association of the 6.7 GHz masers with outflows, based on the similarity of the 3D velocities of the methanol and water masers, agrees with the results by De Buizer (2003) and De Buizer et al (2009), which find that in most cases the methanol masers are elongated parallel to jets traced by the H 2 and SiO emissions, suggesting a physical association of the 6.7 GHz masers with the corresponding outflows.…”
Section: Methanol and Oh Maser Dynamics: Jet-driven Expansion Of The Hmcsupporting
confidence: 89%
“…In Table 5 we list the luminosities, the depth of the 10 μm silicate absorption feature, whether or not any compact H II region is present, and whether or not any outflows have been detected, which can be useful for independently constraining disk geometry. As previously noted, however, in the case of AFGL 4176, no outflow components have been detected (De Buizer 2003;De Buizer et al 2009). For a broader discussion of these and other sources, we refer to the work by Grellmann et al (2011).…”
Section: Comparison With Other Mysossupporting
confidence: 59%
“…3, AFGL 4176 shows evidence for deviations from spherical symmetry only at the scales probed by our mid-infrared interferometric observations, which correspond to scales of roughly 20 to 200 mas. Furthermore, no outflow component has been revealed in searches by De Buizer (2003) and De Buizer et al (2009), nor in the HCO+ data presented in this work (Fig. 8).…”
Section: One-dimensional Radiative Transfer Modelingcontrasting
confidence: 38%
See 1 more Smart Citation
“…Many interferometric observations show that thermal and maser SiO emission depicted the low-velocity outflow centered on source I in Orion KL (Blake et al 1996;Wright et al 1996;Beuther et al 2005;Plambeck et al 2009;Goddi et al 2009;Zapata et al 2009). In addition, SiO traces many other molecular outflows in different sources (Jiménez-Serra et al 2004;Gibb et al 2007;De Buizer et al 2009;Zapata et al 2009). Mookerjea et al (2007) have not found emission from SiO at the position of the hot molecular core in G34.26+0.15.…”
Section: Discussionmentioning
confidence: 99%